Identification and treatment of T2-low asthma in the era of biologics - Kyriakopoulos, Chris; Gogali, Athena; Bartziokas, Konstantinos; Kostikas, Konstantinos (ERJ open research, 2021)
Currently, and based on the development of relevant biologic therapies, T2-high is the most well-defined endotype of asthma. Although much progress has been made in elucidating T2-high inflammation pathways, no specific clinically applicable biomarkers for T2-low asthma have been identified. The therapeutic approach of T2-low asthma is a problem urgently needing resolution, firstly because these patients have poor response to steroids, and secondly because they are not candidates for the newer targeted biologic agents. Thus, there is an unmet need for the identification of biomarkers that can help the diagnosis and endotyping of T2-low asthma. Ongoing investigation is focusing on neutrophilic airway inflammation mediators as therapeutic targets, including interleukin (IL)-8, IL-17, IL-1, IL-6, IL-23 and tumour necrosis factor-α; molecules that target restoration of corticosteroid sensitivity, mainly mitogen-activated protein kinase inhibitors, tyrosine kinase inhibitors and phosphatidylinositol 3-kinase inhibitors; phosphodiesterase (PDE)3 inhibitors that act as bronchodilators and PDE4 inhibitors that have an anti-inflammatory effect; and airway smooth muscle mass attenuation therapies, mainly for patients with paucigranulocytic inflammation. This article aims to review the evidence for noneosinophilic inflammation being a target for therapy in asthma; discuss current and potential future therapeutic approaches, such as novel molecules and biologic agents; and assess clinical trials of licensed drugs in the treatment of T2-low asthma.